CITRUS GUM MATRIX TABLETS FOR SUSTAIN RELEASE OF ACECLOFENAC: IN VITRO DRUG RELEASE AND SWELLING BEHAVIOR - K, VIJAYA SRI; CH, AJAY KUMAR; D, RAVISHANKER (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The main aim of the study was to establish the potential of citrus gum as a novel pharmaceutical aid for the development of sustained release drug delivery systems. Methods: Aceclofenac SR tablets with Citrus gum powder and comparison studies of HPMC K 100 were prepared by wet granulation technique. Compatibility of the drug with the gum was studied using DSC and FTIR. The physicochemical properties such as hardness, thickness, friability, uniformity of weight and the drug content of the formulated tablets were estimated. Results : The comparative dissolution profiles of aceclofenac sustained release tablets prepared with Citrus gum powder (20%) and HPMC K-100 (30%) was shown that the effect of polymer concentration, decrease in drug release rate was observed when citrus gum powder content in the matrix was increased. Conclusion: The sustained release tablets shows that Citrus gum powder by forming a matrix retards the release rate of drug and can be used as sustained release dosage form. Key words: Aceclofenac; Citrus gum powder; sustain release polymer; HPMC K 100; swelling behavior.